Material cultures of music notation
1 online resource (xviii, 212 pages)
Keywords: "Material Cultures of Music Notation brings together a collection of essays that explore a fundamental question in the current landscape of musicology: how can writing and reading music be understood as concrete, material practices in a wider cultural context? Drawing on interdisciplinary approaches from musicology, media studies, performance studies, and more, the chapters in this volume offer a wide array of new perspectives thatforeground the materiality of music notation. From digital scores to the transmission of manuscripts in the Middle Ages, the volume deliberately disrupts boundaries of discipline, historical period, genre, and tradition, by approaching notation's materiality through four key interrelated themes: knowledge, the body, social relations, and technology. Together, the chapters capture vital new work in an essential emerging area of scholarship."--Publisher's description.